Patient´s oral health literacy and associations with sociodemographic, source of information, and oral health variables - Mialhe, Fábio Luiz; Pereira, Pâmela Letícia; Oliveira Júnior, Alcir José de; Cortellazzi , Karine Laura; Soares, Gustavo Hermes (Revista da ABENO, 2022)
The objective of this study was to evaluate the levels of Oral ealth Literacy (OHL) among adult patients attending in a university dental clinic (UDC) and associations with diverse variables. A crosssectional study was conducted with a sample of 312 adult users of a UDC, from February to July 2018. Data collection was done by using a self-administered questionnaire including demographics, HeLD-14 for evaluating OHL, sources for accessing information about oral health, self-rated oral health (SROH), and reasons to look for the dentist. Simple and multiple logistic regression analyses were performed to assess the level of association between independent and dependent variables (OHL). The median value for HeLD-14 was 44.2 (sd=7.8). In the final model, the following users had a significantly higher likelihood of presenting lower OHL levels compared to their counterparts: those with up to elementary school (OR: 3.82, 95%CI: 1.85-7.88), those whose income was less than or equal to 2 Brazilian Minimum Wages (OR: 3.65, 95%CI: 1.37-9.76), those who use television/radio/newspaper/magazines/others as theirmain source of oral health information (OR: 1.97, 95%CI:1.17-3.30), those who classified their SROH as fair/poor (OR: 1.88, 95%CI: 1.08-3.26), and those who had gone to the dentist the last time due to pain/extraction (OR: 2.28, 95%CI: 1.35-3.85). The users’ OHL levels were associated with sociodemographic variables, sources of information, and oral health, a fact that must be considered by dental students and their professors, in the processes of communication and health education with UDC users, to provide better oral health care for them.